1969
DOI: 10.1113/jphysiol.1969.sp008835
|View full text |Cite
|
Sign up to set email alerts
|

The permeation of non‐electrolytes through the single barnacle muscle cell

Abstract: SUFMARYThe rate of movement of non-electrolytes and tritiated water (THO) across the muscle cell membrane of the giant barnacle Balanus nubilus has been studied and permeability coefficient calculated. The rate of permeation is more closely related to the oil-water partition coefficient than to size of the molecule or degree of hydrogen bonding. Calculations based on efflux from an ideal cylinder suggest that the membrane acts as a significant barrier to movement of these molecules. The cell was unable to conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

1970
1970
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 12 publications
3
13
0
Order By: Relevance
“…2) which indicates a higher activation energy at lower temperatures and there are two possible explanations for this: (1) if the area available for diffusion across the membrane decreases as the temperature is lowered, or (2) if the permeability to DMSO is made up from two independent diffusion fluxes which have different activation energies. Unfortunately the former concept is incompatible with the report by Solomon (1968) that the activation energy for the diffusion of tritiated water into the red blood cell of the dog is constant between 7 and 370 C. However, Bunch & Edwards (1969) found that the equivalent pore size of single muscle fibres from the giant barnacle was dependent on temperature in the presence of DMSO, but independent of temperature in the range 4-25' C when either glycerol or urea was used instead of DMSO. These authors reported an increase in equivalent pore radius from 3-5 A at 40 C to 14 A at 25°C, and an extremely high activation energy of 26-1 kcal/mole for the transfer of DMSO across the striated muscle fibre (presumably on the basis of a linear Arrhenius relationship between permeability at 4 and 200 C).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…2) which indicates a higher activation energy at lower temperatures and there are two possible explanations for this: (1) if the area available for diffusion across the membrane decreases as the temperature is lowered, or (2) if the permeability to DMSO is made up from two independent diffusion fluxes which have different activation energies. Unfortunately the former concept is incompatible with the report by Solomon (1968) that the activation energy for the diffusion of tritiated water into the red blood cell of the dog is constant between 7 and 370 C. However, Bunch & Edwards (1969) found that the equivalent pore size of single muscle fibres from the giant barnacle was dependent on temperature in the presence of DMSO, but independent of temperature in the range 4-25' C when either glycerol or urea was used instead of DMSO. These authors reported an increase in equivalent pore radius from 3-5 A at 40 C to 14 A at 25°C, and an extremely high activation energy of 26-1 kcal/mole for the transfer of DMSO across the striated muscle fibre (presumably on the basis of a linear Arrhenius relationship between permeability at 4 and 200 C).…”
Section: Resultsmentioning
confidence: 91%
“…(1) He considered that there were insignificant diffusion delays in extracellular space; however, this is an oversimplification and was not borne out by the present study. (2) He assumed that the cell membrane was perfectly elastic so that the ratio V/A for a cell was simply related to the cell radius; however, recent work on the electron microscopy of smooth muscle fixed in hypertonic solutions does not verify this assumption (C. A. Walter, personal communication) and there is little supporting evidence from experiments with striated muscle fibres under hypertonic conditions (Blinks, 1965 DMSO (20%,w/v), the non-electrolyte had distributed itself uniformly throughout the water space in the muscle; however, Bunch & Edwards (1969) have shown that DMSO would dissolve in only 60 % of the water in barnacle muscle fibres.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Using the value of 0.15 ml/g for V e , calculated earlier, and 4200 cm 2 /g for Sm,,, 14 we then find P mw = 0.41 x 0.15/4200 = 0.15 x 10" 4 cm/ sec. This value is surprisingly low, compared with the dog erythrocyte water permeability of 44 x 10~4 cm/sec, 31 but is not incompatible with that of the squid axon, 1.4 x 10" 4 cm/sec, 32 the barnacle muscle cell, 2.6 x 10~4 cm/sec, 33 the amoeba, 0.23 x 10" 4 cm/sec, 34 or the Bolwig and Lassen estimate for the brain capillary, 0.4 x 10~4 cm/ sec. 7 This limited permeability of the sarcolemma to water probably explains the inability of Suenson et al 35 to explain the transient diffusion of water through a sheet of right ventricle.…”
mentioning
confidence: 98%